Protein arginine methyltransferase 2 (PRMT2) promotes dextran sulfate sodium‐induced colitis by inhibiting the SOCS3 promoter via histone H3R8 asymmetric dimethylation. (16th November 2021) - Li, Jiahong; Pan, Xiaohua; Ren, Zhengnan; Li, Binbin; Liu, He; Wu, Chengfei; Dong, Xiaoliang; de Vos, Paul; Pan, Li‐Long; Sun, Jia
Abstract : Background and Purpose: There is emerging evidence for a critical role for epigenetic modifiers in the development of inflammatory bowel disease (IBD). Protein arginine methyltransferase 2 (PRMT2) is responsible for the methylation of arginine residues on histones and targets transcription factors involved in many cellular processes, including gene transcription, mRNA splicing, cell proliferation, and cell differentiation. In this study, the role and underlying mechanisms of PRMT2 in colitis were studied. Experimental Approach: A mouse dextran sulfate sodium (DSS)‐induced experimental colitis model was used to study PRMT2 in colitis. Lentivirus‐induced PRMT2 silencing or overexpression in vivo was applied to address the role of PRMT2 in colitis. Detailed western blot and expression analysis were done to understand epigenetic changes induced by PRMT2 in colitis. Key Results: PRMT2 is highly expressed in inflammatory bowel disease patients, in inflamed murine colon and in TNF‐α stimulated murine gut epithelial cells. PRMT2 overexpression aggravates, while knockdown alleviates DSS‐induced colitis, suggesting that PRMT2 is a pivotal mediator of colitis in mice. Mechanistically, PRMT2 mediates colitis by increasing repressive histone mark H3R8 asymmetric methylation (H3R8me2a) at the promoter region of the suppressor of cytokine signalling 3 promoter (SOCS3). Resultant inhibition of SOCS3 expression and inhibition of SOCS3‐mediated degradation of TNF receptor associated factor 5 (TRAF5) via ubiquitination led to elevated TRAF5 expression and TRAF5‐mediated downstream NF‐κB/MAPK activation. Conclusion and Implications: Our study demonstrates that PRMT2 acts as a transcriptional co‐activator for proinflammatory genes during colitis. Hence, targeting PRMT2 may provide a novel therapeutic approach for colitis.